Geodynamic evolution of Ossa-Morena Zone in a SW Iberian context during the Variscan cycle - Moreira, Noel (2015)
Ossa-Morena Zone (OMZ) is crucial to understanding the geodynamic evolution of the Variscan cycle in SW Iberia. We review previous data, from Early to Late Paleozoic. The early Cambrian (conglomeratic and felsic metavolcanic units) lies unconformably upon Neoproterozoic formations and shows a carbonate sequence with bimodal volcanic rocks, accompanied by intrusion of plutonic bodies (535–520 Ma). This could be interpreted as result of rifting process (Sánchez-García et al., 2010). The middle Cambrian is marked by a significant crustal stretching episode: siliciclastic sedimentation is accompanied by bimodal volcanism, with transitional alkaline geochemical features, symptomatic of an intra-plate environment. The Cambrian–Ordovician transition is marked by the absence of sedimentation and/or an erosional episode. This period is concomitant with large plutonic intrusions (~ 510–485 Ma). This is related to opening of the Rheic Ocean: geochemical (N- and T-MORB signatures) and geochronological data support the existence of anorogenic oceanic magmatic activity during this period (~ 485–480 Ma). From the Mid Ordovician until the end of Silurian, magmatic features are related to passive margin evolution and tectonic stability.